Optimisation of immobilized pH gradient range for serum proteomic analysis of post Covid-19 syndrome patients using two-dimensional electrophoresis - Badhrulhisham, Aisyah; Mohamed Bakrim, Norbaiyah; Abdullah, Nor Zamzila; Wan Ramli, Wan Nurliyana; Abu Hassan, Salmah Anim; Hamzah, Hairul Aini; Idorus, Mohd Yusri (Biome Scientia Sdn Bhd, 2023)
Discovery of diagnostic protein marker for Post COVID-19 Syndrome (PCS) is vital as currently PCS is a diagnosis of exclusion needing various investigations and time consuming. Two-dimensional electrophoresis (2-DE) is used for proteomic profiling analysis to identify candidate protein markers which is simpler to run, easy to reproduce and cost effective. This study aimed to compare serum proteins profiles between broad and narrow range of immobilized pH gradient (IPG) to optimize 2-DE methods in proteomic analysis of serum PCS patients. Pooled serum of five PCS patients, matched for age, gender and race was cleaned up. Two µg of these extracted proteins were uploaded onto 7 cm of IPG strips pH range of 3-10 and 4-7 respectively. The proteins were separated via the first dimension by isoelectric focusing (IEF) system. The strips then transferred to precast gels and processed for second dimension of protein separation using Sodium dodecyl-sulfate polyacrylamide gel electrophoresis (SDS-PAGE). The gels then stained using Bio safe Coomassiee Stain and distained using miliQ water. The gel images were analysed using PD Quest software. A total of 122 protein spots were detected in 3-10 gel, with most proteins concentrated at the centre region. Using the similar sensitivity parameter, higher protein spots were detected with a total of 261 for pH 4-7 gel with better protein spots intensity and resolution. The intensity of proteins expression was greater in plasma reference gel than the serum 3-10 gel, but the appearance was improved in serum 4-7 gel. In conclusion, for 2-DE proteomic analysis, using an IPG strip of pH 4-7 is recommended for further serum PCS patient proteomic analysis as it yielded more protein spots with better resolution and intensity compared to pH 3-10 as a narrow IPG pH range allows more migration distance between proteins in a more focused pH range.